2014
DOI: 10.1007/s00438-014-0874-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of aquaporin genes (AQPs) in Chinese cabbage (Brassica rapa ssp. pekinensis)

Abstract: Aquaporins (AQPs) are members of a superfamily of integral membrane proteins and play a significant role in the transportation of small molecules across membranes. However, currently little is known about the AQP genes in Chinese cabbage (Brassica rapa ssp. pekinensis). In this study, a genome-wide analysis was carried out to identify the AQP genes in Chinese cabbage. In total, 53 non-redundant AQP genes were identified that were located on all of the 10 chromosomes. The number of AQP genes in Chinese cabbage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 79 publications
7
57
0
Order By: Relevance
“…These results are possible evidence of biased gene loss in the sHSP family of Chinese cabbage, with a whole-genome triplication of two-step origin. Similar results have been observed in other gene families, e.g., AQP (Tao et al, 2014). However, Br18.0B I, Br20.1 ER, and Br16.2 had no syntenic orthologs in A. thaliana, while no syntenic orthologs of At17.6A I, At17.6C I, or At17.8 I were found in Chinese cabbage (Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…These results are possible evidence of biased gene loss in the sHSP family of Chinese cabbage, with a whole-genome triplication of two-step origin. Similar results have been observed in other gene families, e.g., AQP (Tao et al, 2014). However, Br18.0B I, Br20.1 ER, and Br16.2 had no syntenic orthologs in A. thaliana, while no syntenic orthologs of At17.6A I, At17.6C I, or At17.8 I were found in Chinese cabbage (Table 2).…”
Section: Discussionsupporting
confidence: 86%
“…Based on these findings, we concluded that there are 59 functional AQP genes in B. rapa , which we named based on nomenclature used in other plants and guided by sequence similarity and phylogenetic analysis. Tao et al [23] previously reported 53 AQP genes in B. rapa , and our analysis found these, along with six more AQP genes. Additional file 1: Table S1 lists the chromosomal position, ORF length and orthologous genes, as well as predicted protein length, iso-electric point and molecular weight for each of these 59 B. rapa AQP genes.…”
Section: Resultssupporting
confidence: 72%
“…In addition, the ar/R selectivity filter is highly conserved and typical of watertransporting aquaporins (F/H/T/R). The same ar/R selectivity filter sequence is shared by the PIP sub-family in different plant species such as Z. mays, A. thaliana, P. trichocarpa, S. lycopersicum, G. max and B. rapa (Chaumont et al 2001;Johanson et al 2001;Gupta and Sankararamakrishnan 2009;Reuscher et al 2013;Zhang et al 2013;Tao et al 2014). SIn plants,everal researchers hypothesize PIP aquaporins have a central role in roots water absorption in rootsfor plant PIP aquaporins, suggesting thatand this proteins could also actively regulate root and leaf hydraulics (Maurel et al 2008;Li et al 2014).…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%
“…This differential expression could be plant-, aquaporin-, or stress-specific. Differential expression of aquaporins in response to different environmental stresses has been comprehensively evaluated in several plant species such as Arabidopsis, maize, poplar and B. rapa in the past years (Alexandersson et al 2005;Zhu et al 2005;Cohen et al 2013;Tao et al 2014). Regarding common bean, few aquaporins have been characterized to date.…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%